2010
DOI: 10.21273/horttech.20.4.705
|View full text |Cite
|
Sign up to set email alerts
|

Growing Minds: Evaluating the Effect of Gardening on Quality of Life and Physical Activity Level of Older Adults

Abstract: A questionnaire based on the Life Satisfaction Inventory A (LSIA) was used to investigate older adult (age 50+ years) gardeners' and nongardeners' perceptions of personal life satisfaction and levels of physical activity. The LSIA measures five components of quality of life: “zest for life,” “resolution and fortitude,” “congruence between desired and achieved goals,” “physical, psychological, and social self-concept,” and “optimism.” Additional multiple-choice questions were asked to determine responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
4
39
0
1
Order By: Relevance
“…depression severity, life satisfaction, cognitive function) persisted at 3-months' follow up after the therapy, indicating that gardening has a persisting influence on health. Of the 22 case studies, 7 studies focused on daily gardening and found that those who participated had better health than did non-gardeners, such as reductions in stress and BMI, as well as increases in general health and life satisfaction (Park et al, 2009, Sommerfeld et al, 2010, van den Berg et al, 2010, Waliczek et al, 2005, Wilson and Christensen, 2011, Wood et al, 2016, Zick et al, 2013). The strength of these studies is that they found no significant difference in the characteristics or socio-economic status of gardeners and non-gardeners, or controlled for these factors.…”
Section: Discussionmentioning
confidence: 99%
“…depression severity, life satisfaction, cognitive function) persisted at 3-months' follow up after the therapy, indicating that gardening has a persisting influence on health. Of the 22 case studies, 7 studies focused on daily gardening and found that those who participated had better health than did non-gardeners, such as reductions in stress and BMI, as well as increases in general health and life satisfaction (Park et al, 2009, Sommerfeld et al, 2010, van den Berg et al, 2010, Waliczek et al, 2005, Wilson and Christensen, 2011, Wood et al, 2016, Zick et al, 2013). The strength of these studies is that they found no significant difference in the characteristics or socio-economic status of gardeners and non-gardeners, or controlled for these factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the revised SPS, one of the six subscales assesses the psychosocial benefits of gardening [50, 51]. The PSS is used to measure the degree to which situations in an individual’s life are appraised with stress [52].…”
Section: Methodsmentioning
confidence: 99%
“…The target population in this study was adults aged 50 years or older. This age was selected as the definition of an ''older adult'' because it is the standardized age for member acceptance in the AARP [formerly the American Association of Retired Persons (AARP, 2010;Sommerfeld et al, 2010b)]. After Internal Review Board approval, the sample was drawn from two sources.…”
Section: Instrumentationmentioning
confidence: 99%